Low frequency sound speed measurements paired with computed X-ray tomography Imaging in gas-bearing reconstituted natural sediments - Wilson, P; Reed, A; Wood, W; Roy, R (European Acoustics Association, 2007)
One of the difficulties encountered in verifying sound propagation models for gas bearing sediments is determining the overall void fraction (VF) and the bubble size distribution (BSD), both of which greatly effect the acoustic behavior. Traditional time-offlight sound speed measurements are hindered at low frequencies because of the large sample size needed. Due to these difficulties, the various models that have appeared in the literature are essentially unverified by experiment. These issues have been addressed by combining one-dimensional acoustic resonator measurements of sound speed with contemporaneous BSD and VF determination by computed x-ray tomography. Sound speed was successfully measured in reconstituted bay mud and kaolinite sediments containing varying fractions of biogenic gas bubbles or air bubbles. The acoustic resonator operated between 100–2000 Hz and utilized cylindrical acrylic core liners to contain the sediment. Because of the compliance of the core liner walls, an elastic waveguide model was used to relate the sound speed measured inside the core liner to that which would be observed in the free field. The measured sound speeds ranged from 1520 m/s for gas-free mud to as low as 287 m/s for gassy mud and 114 m/s for gassy kaolinite. Volumetric images produced from x-ray CT scans yielded a void fraction of 0.0045 in the kaolinite sample and void fractions ranging from 0.0014 to 0.0024 in the reconstituted bay mud. For the kaolinite, the measured sound speeds showed negligible dispersion and were accurately described by Wood’s effective medium model, which for the void fractions encountered is dependent only upon the ambient pressure, the void fraction, the sediment’s bulk mass density, and the assumption that all the bubbles are smaller than resonance size at the highest frequency of interest.